The Effect Of Knowledge Management On Competitive Advantage With Organisational Culture As A Mediator In Malaysian Construction Companies - Virgiyanti, Wiwied (2014)
This study investigates the relationship between knowledge management processes, organisational culture, and competitive advantage in construction companies in Malaysia. Its main objective is to empirically investigate the mediating effect of organisational culture on the relationship between knowledge management and competitive advantage. Additionally, it was meant to investigate the relationship between knowledge management and organisational culture, knowledge management and competitive advantage, and determine the dominant culture type in construction companies in Malaysia. Using simple random sampling, 84 CIDB Malaysia’s Grade 7 construction companies were sampled, from 4,462 of total population from West and East Malaysia. The sample size was justified with Post-Hoc Power Analysis using G*Power to calculate the appropriateness of sample size. The research instruments used were the questionnaire based on Lawson (2003), Cameron and Quinn (2006), and Byrd and Turner (2001). The main data analysis was performed using structural equation modelling (SEM) – partial least squares (PLS). The findings indicate that organisational culture partially mediates the relationship between knowledge management processes and competitive advantage. The findings also indicate that there is a significant relationship between knowledge management processes and organisational culture, and positive relationship between knowledge management processes and competitive advantage. The last finding shows that clan culture is the dominant culture type in Malaysian construction companies.